Transformations in transit: reconstitution of gender identity among Moldovan domestic workers in Istanbul households - Ünal, Rahime Arzu. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2006., 2006)
This thesis aims to analyze the reconstitution of gender identities of Moldovan domestic workers and changing practices of womanhood, as a result of transnational migration. It shows how their ongoing journeys between Moldova and Turkey transform their understandings of their female identities, which they constitute both in relation to their past experiences and to their practices of transmigrancy. In their experience of migration, women create new networks and reconstitute their identities by differentiating themselves from or aligning themselves with the others whom they come into contact with and engage in mutual conversations. By focusing on the ongoing struggles of Moldovan women over the meanings of ideal motherhood and housekeeping in these conversations, I argue that the migration of Moldovan women brings different ideas of womanhood together. They reconstitute resisting subjectivities through dismantling and redefining meanings of “ideal” womanhood in relation to multiple affiliations and practices in a transnational field. This transnational field within which they operate gives rise to a variety of different understandings of femininity, strategically employed, in contrast to a hegemonic global definition of gendered identity.
Keywords: Women immigrants -- Turkey.; Women -- Employment -- Foreign countries.; Moldavia (Romania) -- Employment -- Foreign countries.